2013
DOI: 10.1002/cctc.201300640
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Preparation of δ‐Valerolactones with Horse Liver Alcohol Dehydrogenase

Abstract: The direct aldol polymerization of acetaldehyde, a new approach for the synthesis of poly(vinyl alcohol)‐ and poly(vinyl alcohol‐co‐ethylene)‐type oligomers, cooperatively catalyzed by organocatalysts and Brønsted acids was investigated. Thus, we successfully obtained oligomers that contain a substantial amount of 1,3‐hydroxy groups in the main chain. This conceptually new approach is an important step towards realizing the one‐step synthesis of poly(vinyl alcohol)s from acetaldehyde with perfect atom economy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 79 publications
(62 reference statements)
2
6
0
Order By: Relevance
“…The transformation of 7a was completed within 6 h, which was much faster than that of 8a and 9a (36 h and 72 h) (Table 2, entries 7-9), which suggested that the substrate with larger substituent group binds less efficiently in the active site of enzyme pocket. In terms of product chirality, this catalytic system proceeded with stereoselectivity towards the (S)-enantiomer, which is in accordance with the rule of preferred stereoselectivity of HLADH (Díaz-Rodríguez et al 2014;Kara et al 2013). For the reaction of 7a and 8a, as high as > 95% ee was observed in the present catalytic system (Additional file 1: Figures S12 and S13).…”
Section: Substrate Scope Expandingsupporting
confidence: 85%
“…The transformation of 7a was completed within 6 h, which was much faster than that of 8a and 9a (36 h and 72 h) (Table 2, entries 7-9), which suggested that the substrate with larger substituent group binds less efficiently in the active site of enzyme pocket. In terms of product chirality, this catalytic system proceeded with stereoselectivity towards the (S)-enantiomer, which is in accordance with the rule of preferred stereoselectivity of HLADH (Díaz-Rodríguez et al 2014;Kara et al 2013). For the reaction of 7a and 8a, as high as > 95% ee was observed in the present catalytic system (Additional file 1: Figures S12 and S13).…”
Section: Substrate Scope Expandingsupporting
confidence: 85%
“…[110] (HLADH) and other ADHs for the (enantioselective) oxidative lactonisation of various diols. [114] Oxidative lactonisation reactions of diols have also been reported with the laccase-TEMPO system. [115] As the alcohol oxidation step is non-enzymatic,any chiral discrimination can be excluded.…”
Section: Oxidation Of Primary Alcohols To Acidsmentioning
confidence: 99%
“…epoxide or lactone products. 14,111,112,114,[304][305][306] Furthermore, high product concentrations in easily water separable organic phases will also facilitate DSP (vide infra).…”
Section: How Green/environmentally Friendly Are Biocatalytic Oxyfunctmentioning
confidence: 99%